2001
DOI: 10.1046/j.1440-1754.2001.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactase deficiency among Malaysian children with recurrent abdominal pain

Abstract: The prevalence of lactase deficiency among this group of Malaysian children with recurrent abdominal pain was high, but lactase deficiency did not appear to play an important role in causing the symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…This was an unexpected finding, since studies on non-autistic children involving patients of both sexes did not mention differences in lactase activity between boys and girls (Lebenthal et al, 1975;Gupta et al, 1999). A study on Malaysian children (Boey, 2001) demonstrated a similar proportion of boys and girls with lactase deficiency (71.4% and 70%, respectively). The biologic relevance for this observation is unclear and the small number of girls (n = 14) may have influenced statistical outcome.…”
Section: Discussionmentioning
confidence: 91%
“…This was an unexpected finding, since studies on non-autistic children involving patients of both sexes did not mention differences in lactase activity between boys and girls (Lebenthal et al, 1975;Gupta et al, 1999). A study on Malaysian children (Boey, 2001) demonstrated a similar proportion of boys and girls with lactase deficiency (71.4% and 70%, respectively). The biologic relevance for this observation is unclear and the small number of girls (n = 14) may have influenced statistical outcome.…”
Section: Discussionmentioning
confidence: 91%
“…(10,11) The most common carbohydrate is lactose, which is found in mammalian milk. The onset of lactose intolerance is insidious and the affected patients may not realise that lactose is the culprit of their abdominal pain, as the pain only appears a few hours after milk ingestion.…”
Section: Carbohydrate Intolerancementioning
confidence: 99%
“…A constipação intestinal funcional pode cursar com DAR, mas a sua relação com o hábito intestinal deverá contribuir para o diagnóstico e orientação do caso. Estudos controlados não demonstraram a associação entre DAR e deficiência de lactase, assim, dietas de exclusão, sem comprovação diagnóstica, devem ser evitadas 10,11,22 . Da mesma forma, mais recentemente, não foi comprovada a relação entre DAR e doença celíaca 23 .…”
Section: Dor Abdominal Recorrente -Darunclassified